Inovação no sistema de informações gerenciais: o caso do Colégio Politécnico da UFSM - Barros, Cristiano Gattermann de (2018)
The present study search to evaluate the system of Solicitation of Demands in Projects – SDP, based in the perceptions of the users of this system, and, based in this evaluation propose innovations that may improve the process of budgetary planning, executing and controlling of the institution. The research is guided by the idea that the innovation in process in the public sector, using Information and Communication Technologies may contribute to increase the quality of the service delivered to the population, through a budgetary process more agile, practical and transparent. In order to achieve this goal, it was realized a case study in the Colégio Politécnico da UFSM, unity that created the SDP to plan, execute and control its budget. The activities related to the budgetary process of the unity were observed, and it was elaborated and applied a survey with the users of the system, in other words, the proponents of projects, searching to better comprehend how the system can become more efficient and evaluate the perception of this users about the system. In order to process the data obtained in the survey, it where made frequency and mean analysis, comparisons of means using t test, and reliability tests using Cronbach alpha. After analyzing the results found, it where observed that the use of SDP has contributed to improve the budget process in the institution, and that the users have a very positive perception about the system.